Pancreatico‐jejunostomy decreases post‐operative pancreatic fistula incidence and severity after central pancreatectomy. Issue 1 (15th August 2017) - Borel, Frédéric; Ouaissi, Mehdi; Merdrignac, Aude; Venara, Aurelien; De Franco, Valéria; Sulpice, Laurent; Hamy, Antoine; Regenet, Nicolas
Abstract : Backgrounds: Central pancreatectomy (CP) is an alternative to pancreaticoduodenectomy and distal pancreatectomy in benign tumours of pancreatic isthmus management. It is known for a high post‐operative pancreatic fistula (POPF) rate. The purpose of this study was to compare POPF incidence between pancreatico‐jejunostomy (PJ) and pancreatico‐gastrostomy (PG). Methods: Fifty‐eight patients (mean age 53.9 ± 1.9 years) who underwent a CP in four French University Hospitals from 1988 to 2011 were analysed. The distal pancreatic remnant was either anastomosed to the stomach (44.8%, n = 25) or to a Roux‐en‐Y jejunal loop (55.2%, n = 35) with routine external drainage allowing a systematic search for POPF. POPF severity was classified according to the International Study Group on Pancreatic Fistula (ISGPF) and Clavien‐Dindo classifications. Results: The groups were similar on sex ratio, mean age, ASA score, pancreas texture, operative time and operative blood loss. Mean follow‐up was 36.2 ± 3.9 months. POPF were significantly more frequent after PG (76.9 versus 37.5%, P = 0.003). PG was associated with significantly higher grade of POPF both when graded with ISGPF classification ( P = 0.012) and Clavien‐Dindo classification ( P = 0.044). There was no significant difference in post‐operative bleeding (0.918) and delayed gastric emptying (0.877) between the two groups. Hospital length of stay was increased after PG (23.6 ± 3.5 days versus 16.5 ± 1.9 days, P = 0.071). There was no significant difference in incidence of long‐term exocrine (3.8 versus 19.2%, P = 0.134) and endocrine (7.7 versus 9.4%, P = 0.575) pancreatic insufficiencies. Conclusion: PG was associated with a significantly higher POPF incidence and severity in CP. We recommend performing PJ especially in older patients to improve CP outcomes.